Ammonia removal from thermal hydrolysis dewatering liquors via three different deammonification technologies - Ochs, Pascal; Martin, Benjamin D.; Germain, Eve; Stephenson, Tom; van Loosdrecht, Mark C. M.; Soares, Ana (Elsevier, 2020)
The benefits of deammonification to remove nitrogen from sidestreams, i.e., sludge dewatering liquors, in municipal wastewater treatment plants are well accepted. The ammonia removal from dewatering liquors originated from thermal hydrolysis/anaerobic digestion (THP/AD) are deemed challenging. Many different commercial technologies have been applied to remove ammonia from sidestreams, varying in reactor design, biomass growth form and instrumentation and control strategy. Four technologies were tested (a deammonification suspended sludge sequencing batch reactor (S-SBR), a deammonification moving bed biofilm reactor (MEDIA), a deammonification granular sludge sequencing batch reactor (G-SBR), and a nitrification suspended sludge sequencing batch reactor (N-SBR)). All technologies relied on distinct control strategies that actuated on the feed flow leading to a range of different ammonia loading rates. Periods of poor performance were displayed by all technologies and related to imbalances in the chain of deammonification reactions subsequently effecting both load and removal. The S-SBR was most robust, not presenting these imbalances. The S-SBR and G-SBR presented the highest nitrogen removal rates (NRR) of 0.58 and 0.56 kg N m−3 d−1, respectively. The MEDIA and the N-SBR presented an NRR of 0.17 and 0.07 kg N m−3 d−1, respectively. This study demonstrated stable ammonia removal from THP/AD dewatering liquors and did not observe toxicity in the nitrogen removal technologies tested. It was identified that instrumentation and control strategy was the main contributor that enabled higher stability and NRR. Overall, this study provides support in selecting a suitable biological nitrogen removal technology for the treatment of sludge dewatering liquors from THP/AD
Keywords: Granular sludge; Suspended sludge; Moving bed biofilm reactor; Sequencing batch reactor; THP/AD; Thermal hydrolysis process; Deammonification